Rational Design of Microfabricated Electroconductive Hydrogels for Biomedical Applications - Walker, Brian W. (Prog Polym Sci, 2019)
Electroconductive hydrogels (ECHs) are highly hydrated 3D networks generated through the incorporation of conductive polymers, nanoparticles, and other conductive materials into polymeric hydrogels. ECHs combine several advantageous properties of inherently conductive materials with the highly tunable physical and biochemical properties of hydrogels. Recently, the development of biocompatible ECHs has been investigated for various biomedical applications, such as tissue engineering, drug delivery, biosensors, flexible electronics, and other implantable medical devices. Several methods for the synthesis of ECHs have been reported, which include the incorporation of electrically conductive materials such as gold and silver nanoparticles, graphene, and carbon nanotubes, as well as various conductive polymers (CPs), such as polyaniline, polypyrrole, and poly(3,4-ethylenedioxyythiophene) into hydrogel networks. Theses electroconductive composite hydrogels can be used as scaffolds with high swellability, tunable mechanical properties, and the capability to support cell growth both in vitro and in vivo. Furthermore, recent advancements in microfabrication techniques such as three dimensional (3D) bioprinting, micropatterning, and electrospinning have led to the development of ECHs with biomimetic microarchitectures that reproduce the characteristics of the native extracellular matrix (ECM). In addition, smart ECHs with controlled structures and healing properties have also been engineered into devices with prolonged half-lives and increased durability. The combination of sophisticated synthesis chemistries and modern microfabrication techniques have led to engineer smart ECHs with advanced architectures, geometries, and functionalities that are being increasingly used in drug delivery systems, biosensors, tissue engineering, and soft electronics. In this review, we will summarize different strategies to synthesize conductive biomaterials. We will also discuss the advanced microfabrication techniques used to fabricate ECHs with complex 3D architectures, as well as various biomedical applications of microfabricated ECHs.